Peripheral Rural Areas around Poznań and Their Value Measured with Economic Indicators - Aleksandra Godek; Marek Pietrucki (Barometr Regionalny, 2015)
In the era of consumption — appropriation of rural areas located in the metropolitan region of Poznań it seems reasonable to estimate their material value. According to authors of publications on environmental services: Mizgajski, Lowicki, and authors discussing problems of sustainable development of rural areas in Poland, such as Kistowski, Matczak, and Myga-Piątek, the economic value of the natural environment is important from the point of view of geographical environment management, both at the local and regional level. The example of peripheral areas in the metropolitan region of Poznań serves to allow the authors of this study to present the approach of preparation of an economic card for the efficiency of agricultural space. The research objective was to present an evaluation of economic opportunities achievable with different classes of soils that are subject to subsequent transformations to a non-agricultural land use. The estimation of economic values based on indicators of costs and income from 1 ha of arable land, and their comparison to the indicators included in projections of financial results made for local spatial development plans allow determination of the actual value of rural areas which, as a result of suburbanization, were consumed by residential and economic stimulation.